Pengembangan Digitalisasi Inovasi Produk UMKM Rinjing Dalam Meningkatkan Penjualan Di Desa Dimoro - Winarsih; Arnia Wijias Wati (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2022)
Background: The development of Small and Medium Enterprises (SMEs) is very rapid in increasing product innovation of woven bamboo rinjing in the village of Kuta, Dimoro as a support for the household income of the local community by utilizing bamboo raw materials which are widely used to make woven bamboo handicraft businesses by woven one by one by forming a circle pattern. Micro, Small and Medium Enterprises is a business unit that plays an important role in economic growth and development as well as the welfare of the Indonesian people. UMKM in Dimoro village in this study also face many obstacles or problems that require various critical solutions to get out of the problems they are facing, although some can run quite smoothly. Rinjing is an item that meets the needs of household appliances, especially in the kitchen. Purpose: this research aims to develop and preserve the woven bamboo rinjing product business in improving product marketing by developing product innovation in community creativity, so that business networks can develop rapidly. Method: This study used a qualitative method which was carried out through observation and interviews with the object directly, namely the business owner of woven bamboo rinjing in the village of Dimoro. This method aims to obtain more complete information about the development of woven bamboo rinjing products in terms of innovation, marketing and business networks that can increase the income of the local community. Conclusion: From the results of observations and interviews conducted, it can be concluded that in business it is also required to innovate, this is done to adapt to increasingly modern developments supported by increasingly advanced levels of technological development so that UMKM must also be creative and innovative in creating product innovation so that the product has an appeal to consumers, so that the product influences the buyer's decision. Suggestion: In this research there is still a lack of innovation in products so that sales are still not optimal and the marketing strategy still needs to be improved by utilizing technology and the need for an extensive network to introduce these products so that they are known to the wider community and to preserve cultural heritage to continue to be preserved as local wisdom. There are still many limitations in this study to be developed in further research.